Ofer coroana.Urgeeent.
Anexe:
Răspunsuri la întrebare
Răspuns de
0
B) 14 supra 23x
...........…………………………………………………
...........…………………………………………………
Răspuns de
0
a) 2 - 3x/x²-x + 2/x -1 + 5/3x =
3(2 - 3x)/3x(x -1) + 6x/3x(x -1) + 5(x -1)/3x(x -1) =
6 - 9x + 6x +5x - 5 totul supra 3x(x-1)=
2x + 1/3x(x - 1)
b) x - 1/(x - 2) - (x + 3)/(x + 2) + 2/(x² - 4) =
(x - 1)(x + 2)/(x² - 4) - (x + 3)(x - 2)/(x² - 4) + 2/(x² - 4) =
x² + x - 2 - x² - x + 6 + 2 totul supra (x² - 4) =
6/x² - 4
c) (2x - 5)(3x + 1) - (2x + 3)(3x - 1) + (2x + 8) totul supra (9x² - 1) =
10x² - 13x - 5 - 6x² - 7x + 3 + 2x + 8 totul supra (9x² - 1) =
4x² - 18x + 6 totul supra 9x² - 1 =
2(2x² - 9x + 3)/9x² - 1
d) 3(3x + 1) - 2x(x + 2) + (x - 3)(2x - 1) totul supra 6x(x - 3) =
9x + 3 - 2x² - 4x + 2x² - 7x + 3 totul supra 6x(x - 3) =
- 2x + 6/ 6x(x - 3) =
2(x - 3)/6x(x - 3) =
1/3x
3(2 - 3x)/3x(x -1) + 6x/3x(x -1) + 5(x -1)/3x(x -1) =
6 - 9x + 6x +5x - 5 totul supra 3x(x-1)=
2x + 1/3x(x - 1)
b) x - 1/(x - 2) - (x + 3)/(x + 2) + 2/(x² - 4) =
(x - 1)(x + 2)/(x² - 4) - (x + 3)(x - 2)/(x² - 4) + 2/(x² - 4) =
x² + x - 2 - x² - x + 6 + 2 totul supra (x² - 4) =
6/x² - 4
c) (2x - 5)(3x + 1) - (2x + 3)(3x - 1) + (2x + 8) totul supra (9x² - 1) =
10x² - 13x - 5 - 6x² - 7x + 3 + 2x + 8 totul supra (9x² - 1) =
4x² - 18x + 6 totul supra 9x² - 1 =
2(2x² - 9x + 3)/9x² - 1
d) 3(3x + 1) - 2x(x + 2) + (x - 3)(2x - 1) totul supra 6x(x - 3) =
9x + 3 - 2x² - 4x + 2x² - 7x + 3 totul supra 6x(x - 3) =
- 2x + 6/ 6x(x - 3) =
2(x - 3)/6x(x - 3) =
1/3x
Alte întrebări interesante
Informatică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă